Factors to be considered in choosing appropriate test statistics (2017)
In this write up, the researcher stated that there are seven factors to be put into consideration in the course of choosing appropriate test statistics in analysing data. The factors are: considering the research topic/titie, research design, hypothesis/research wordings, past research work, nature and arrangement of data, and scales of measurement which the data to be analysed belong to and finally by consulting the experts. Furthermore, the conditions in which each of the test statistics can be used are also stated.